'It’s just nice not to be on screens’: exploring the relationship between pottery making, eudemonic wellbeing, and Instagram - O'Brien, C (Taylor & Francis, 2023)

(untitled)
Since the mid-nineteenth century Arts and Crafts Movement in Britain and its subsequent revivals, craft has been positioned in opposition to new technologies. Yet, increasingly people learn, share, produce, and consume crafts through engagements online. This article discusses the relationship between pottery making, eudemonic wellbeing, and the social media site Instagram in the context of digital ethnographic research with British potters during the COVID-19 pandemic. When physical access to spaces such as studios was limited, these potters turned to digital and social media to learn new skills and connect with others from within their own homes. Central to this article is the dissonance between my participants’ belief that pottery offered them an escape from their phones, yet simultaneously, much of their enjoyment of pottery came from their participation in online spaces, particularly Instagram. The eudemonic wellbeing impacts generated through their engagements with pottery and the online resources and communities associated with it, concern, 1) satisfying work: self-fulfilment and empowerment, and 2) crafting the self: identity, belonging, and social connectedness, as well as a discussion of the stress and negative consequences engagements with social media brought about for several of my participants.